The Prognostic Effect of Thrombocytopenia on the Clinical Severity in COVID-19 Patients - Mirtaher, Fatemeh Sadat; Bagheri, Leyla; Farahbakhsh, Mohammad; Bozorgmehr, Rama; Ebrahimibagha, Hamed; Ghazizadeh, Maryam (Novelty in Biomedicine, 2026)
Background: Thrombocytopenia is associated with the severity and increased morbidity and mortality of COVID-19. Therefore, understanding this association can aid in diagnosing the disease, predicting outcomes, and reducing mortality and morbidity. Materials and Methods: Patient data from the teaching hospital's archives were considered. The severity of the disease was classified into four categories: mild, moderate, severe, and very severe, based on the national protocol. A total of 82 patients were analyzed, including 41 with thrombocytopenia and 41 without, who were admitted to the teaching hospital from February 2021 to the end of March 2022. This allowed for a comparative analysis. Results: Thrombocytopenia was significantly associated with longer hospital stays (p<0.001) of more than 5 days. Thrombocytopenic patients were more likely to be admitted to the ICU (90.2%) compared to non-thrombocytopenic patients (14.6%) (p<0.0001). Thrombocytopenic patients also had lower SpO2, with values below 90% in 90.2% of cases (p=0.046). Thrombocytopenia was linked to DIC and ARDS and had a substantial impact on disease outcome, with mortality rates of 75.6% and 7.3% in thrombocytopenic and non-thrombocytopenic patients, respectively. Severity and various laboratory variables (LDH, D-dimer, CRP, and CPK) also showed significant differences between the two groups. The association between thrombocytopenia and disease severity was significant, with 75.6% categorized as very severe and 22% as severe (p<0.0001). Conclusion: The study found a clear correlation between hospital stay length and admission location for both patient groups. In the ICU, thrombocytopenic patients experience longer stays and lower SpO2 levels. Thrombocytopenia significantly impacts disease outcome and is closely linked to DIC and ARDS, with an increased risk of mortality. Notable differences exist in LDH, D-dimer, CRP, and CPK levels between the two groups. Thrombocytopenia is associated with higher disease severity, particularly in thrombocytopenic patients. Age, gender, hospital stay length, and disease severity correlate meaningfully. Male patients and those with higher clinical severity tend to have longer stays. Additionally, SpO2 levels, respiratory rate, DIC, disease outcome, CPK, and clinical severity are significantly related.